Status of false smut of rice in different districts of West Bengal - Thapa, Sukram; Mahapatra, Sunita; Baral, Deewakar; Lama, Achal; Shivakoty, Pravesh; Das, Srikanta (ORYZA-An International Journal of Rice, 2022)
False smut of rice which was considered a minor disease of rice is presently spreading in most of the rice growing areas of the world causing reduction in yield and quality of the produce. West Bengal is the largest producer with largest area under rice in India. No survey on severity of rice false smut disease in West Bengal has been conducted. Therefore, in attempt to get the idea of false smut disease situation in the state, a survey was conducted in 31 blocks from 8 different districts of West Bengal during the year 2017 from the end of October to first week of December. Number of infected tillers per m2 and number of smut balls per panicle was observed during the survey. False smut symptom was observed in all the plains of West Bengal whereas in hilly areas of the state was found to have no incidence of the disease. During the survey average number of infected tillers ranged from 2.00 to 14.60 numbers of infected tillers / m2. Similarly average number of smutted ball / panicle ranged from 1.21 to 5.32 number of spore ball per panicle.